2014
DOI: 10.1063/1.4879825
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet emission and confinement of tin plasmas in the presence of a magnetic field

Abstract: We investigated the role of a guiding magnetic field on extreme ultraviolet (EUV) and ion emission from a laser produced Sn plasma for various laser pulse duration and intensity. For producing plasmas, planar slabs of pure Sn were irradiated with 1064 nm, Nd:YAG laser pulses with varying pulse duration (5–15 ns) and intensity. A magnetic trap was fabricated with the use of two neodymium permanent magnets which provided a magnetic field strength ∼0.5 T along the plume expansion direction. Our results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…This configuration can be achieved by using two parallel magnets, which generate a magnetic field which is either transverse [24][25][26] or parallel [27][28][29] to the axial direction of the expanding laser plasma plume. Harilal et al 24 reported on the plasma dynamics and optical emission of an Al laser-produced plasma propagating in an almost uniform transverse ∼0.6 T magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This configuration can be achieved by using two parallel magnets, which generate a magnetic field which is either transverse [24][25][26] or parallel [27][28][29] to the axial direction of the expanding laser plasma plume. Harilal et al 24 reported on the plasma dynamics and optical emission of an Al laser-produced plasma propagating in an almost uniform transverse ∼0.6 T magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Pagano and Lunney 27 observed lateral confinement effects on a Cu laser-produced plasma propagating in a ∼ 0.3 T axial magnetic field, and reported an enhancement in the on-axis ion beam emission. Roy et al 28 investigated the extreme ultraviolet emission (EUV) of a Sn laser-produced plasma expanding in a 0.5 T axial magnetic field, in high vacuum. Although no significant effect on the EUV emission was observed, the off-axis ion beam emission was significantly reduced in the presence of the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-produced tin plasma has come up as a most promising and energy-efficient next generation EUV light source for the semiconductor lithography industry (Bakshi, 2009;Roy et al, 2014a;2014b). A high-brightness and debris-free source emitting at 13.5 nm radiation with 2% bandwidth (in-band) is necessary for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of inertial fusion, confinement of the expanding target plasma using a B-field offers a potential means to slow high-energy particles before they implant in the surrounding structures. The B-field is also used for controlling or diverting ion debris in extreme ultraviolet (EUV) lithography laser-produced plasma (LPP) sources (Harilal et al, 2006;Roy et al, 2014a;2014b).…”
Section: Introductionmentioning
confidence: 99%